1994
DOI: 10.1111/j.1528-1157.1994.tb02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Effects on Afterdischarge, Memory Retrieval, and Conditioned Avoidance Response Latency in Hippocampally Kindled Cats

Abstract: Carbamazepine (CBZ) effects on (a) complex partial seizures and afterdischarges (AD), (b) memory retrieval, and (c) conditioned avoidance response (CAR) latencies were studied in a group of 9 hippocampally kindled cats. Significant AD and epileptic seizure suppression was observed in kindled cats after administration of CBZ concurrent with significant improvement in percentage scores on the memory retrieval test. The CAR latencies were longer in kindled cats with or without CBZ than in the conditioned group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Other preclinical studies have demonstrated that CBZ improves the memory in passive-avoidance tests, T-maze (18), and Y-maze (8). Kindled cats treated over the long term with CBZ improved the performance during an active avoidance test with a better control of seizures (7). Rostock et al (19) reported that low doses of CBZ administered to rats were able to reverse amnesia induced by electroconvulsive shock as well as to improve learning during an active avoidance test in rats treated with repeated doses of ethanol.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other preclinical studies have demonstrated that CBZ improves the memory in passive-avoidance tests, T-maze (18), and Y-maze (8). Kindled cats treated over the long term with CBZ improved the performance during an active avoidance test with a better control of seizures (7). Rostock et al (19) reported that low doses of CBZ administered to rats were able to reverse amnesia induced by electroconvulsive shock as well as to improve learning during an active avoidance test in rats treated with repeated doses of ethanol.…”
Section: Discussionmentioning
confidence: 93%
“…In preclinical studies, spatial memory of temporal lobe epileptic rats is shown to be compromised (5,6). Light-discrimination tasks and Y-maze performance also are impaired in epileptic animals, and CBZ reverses these difficulties (7,8). A distinct type of nonassociative and nonspatial memory may be tested in rats through the spontaneous object recognition test (SORT), in which animals must discriminate between familiar and nonfamiliar objects (9) (nonmatching).…”
mentioning
confidence: 99%
“…Rostock et al [115] reported that administration of low doses of CBZ was able to reverse amnesia induced by electroconvulsive shock as well as improve learning during an active avoidance test treated with repeated doses with ethanol. Preclinical studies revealed that CBZ improved memory in passive avoidance tests, T‐maze, and Y‐maze [116], decreased light discrimination task performance and Y‐maze performance in epileptic animals [117], and improved memory, as demonstrated by Morris test after 7–14 days of treatment [118]. In utero studies revealed that CBZ monotherapy with serum maternal levels within the reference ranges did not impair intelligence of the exposed children [119].…”
Section: Cognitive States With Antiepileptic Medicationsmentioning
confidence: 99%
“…This method has I 1 I FIGURE 2. vpa and the six torsional angles used for conformational search. T~: C, -C, -C, -C , , T~: C, -c3-c4-cc,, 7,: cg-c5-c4-cs, T4: C , -~C , -C,-c,, been largely used to explain the spectroscopic shifts in the uv-visible spectra of several chromophores [22,28,291. In the case we are dealing with, the comparison of the structural characteristics of the vpa analogues, optimized with and without the inclusion of solvent effects, indicates no conformational changes induced by the cyclohexane environment that might be reflected in significant changes in the electronic descriptors (Table I).…”
Section: On the Calculation Of The Electronic Descriptorsmentioning
confidence: 99%
“…Dealing with enzyme or receptor inhibition mechanisms, the question of how the protein environment affects the conformation of the active structures arises. We have analyzed the effect that the surrounding protein, modeled as a dielectric continuum (cyclohexane [ 22]), can have on the electronic descriptors. Conformational changes when the drug diffuses into the protein, before binding to the active site, are discussed.…”
mentioning
confidence: 99%